Wandering souls: Protestant migrations in America, 1630 - 1865 - Rohrer, S. Scott (Univ. of North Carolina Press, 2010)
Part I: Migration in America -- Introduction: An overview of Protestant migrations, 1630-1865 -- The first frontier : Thomas Hooker and the New England Puritans -- Part II: The Protestant sojourner -- Migration and the new birth : Devereux Jarratt and the Anglicans of Virginia -- Ethnicity and mobility : Scotch-Irish Presbyterians in eighteenth-century America -- Land and family : the pietist migration to North Carolina in the late Colonial Period -- Reform and the missionary drive : Methodists in the Ohio Country -- Part III: Journeys of the pure -- The dissenters : Baptists and Congregationalists in a separatist world -- God's chosen sojourners : the inspirationists of Amana, Iowa -- An American exodus : Mormons and the westward trek